The Role of Knowledge Creation as a Mediation on the Influence of Talent Management on Innovation Performance - Ekhsan, Muhamad; Suwandi, Suwandi (Trigin Publisher, 2024)
This study explores the mediating role of knowledge creation in the relationship between talent management and innovation performance within Indonesian companies. In the context of a dynamic business environment, organizations are challenged to optimize their talent management strategies not only to enhance individual capabilities but also to foster organizational innovation. Using a quantitative approach and Partial Least Squares Structural Equation Modeling (PLS-SEM), data were collected from 91 respondents across technology, manufacturing, and research-based sectors. The results reveal that talent management significantly influences knowledge creation and innovation performance, while knowledge creation mediates the relationship between talent management and innovation outcomes. These findings highlight the strategic importance of integrating talent development with knowledge-based practices to enhance organizational competitiveness. The study contributes to the theoretical discourse by offering a model that links talent management, knowledge creation, and innovation performance, and provides practical implications for companies seeking to strengthen their innovation capacity in the digital era.